Lake expansion elevates equilibrium diversity via increasing colonization. (9th July 2020) - Hauffe, Torsten; Delicado, Diana; Etienne, Rampal S.; Valente, Luis
Abstract: Aim: Rates of colonization, speciation and extinction determine species richness and endemism in insular systems. The general dynamic model of island biogeography (GDM) predicts that speciation and extinction rates depend on island area and elevation via their control on ecological limits to diversification and therefore covary with an island's geological history. Additionally, the colonization rate may increase with area and elevation through the 'target effect', which can be mediated by reduced 'environmental filtering'. Here we test whether the area and depth expansion of an island‐like ecosystem, a lake, caused a shift in diversity dynamics. Location: Lake Biwa, Japan, whose geological history and biota are well documented. Taxon: Fishes. Methods: We extended the phylogenetic island biogeography framework DAISIE (Dynamic Assembly of Island biota through Speciation, Immigration and Extinction) to accommodate time‐shifts in macroevolutionary rates and in carrying capacity. Using phylogenetic information on colonization and speciation times for the complete Lake Biwa fish community (70 taxa), we tested for a shift in macroevolutionary assembly rates and reconstructed the temporal diversity trajectory in the lake. We assessed the power to identify a shift through a wide range of scenarios and benchmarked against simulated fossil records. Results: We detected an increase in colonization rate of fishes at 0.2 million years ago (Ma), with limited support for the existence of ecological limits. The reconstructed diversity trajectory was close to a source‐sink equilibrium diversity prior to the shift and remained well below a new shift‐driven elevated equilibrium thereafter. We found sufficient power to identify an increase in colonization rate up to 1.5 Ma, whereas extinction concealed the signal of earlier shifts. Main conclusions: The fish diversity dynamics of Lake Biwa show a response to changes in area and depth and phylogenies carry a signature of these changes. The detected increase in colonization rate following Lake Biwa's expansion, elevating the fish diversity, is unlikely due to a predicted increase in ecological limits feeding back on colonization rate. We therefore call for (additional) explanations: the target effect, whereby larger islands attract more species, and reduced environmental filtering due to higher habitat diversity associated with increased lake area/depth.